« Aimez vos ennemis » – une utopie devenue réalité (passagère) en Pologne - Nowicki, Joanna (Studies in religion, 2021)
In this article, we retrace the history of a doctrine that stems from Christian ethics and which, for a while in Poland’s recent history, was translated into a political project. It is expressed in the injunction: “Love your enemies” taken up by the anti-communist dissidents who were inspired by a long national tradition, but who also reacted against the spirit of struggle (of the enemy classes) advocated by the falsely peaceful regime they were fighting. This path led to a policy of reconciliation and forgiveness carried by the personalist Tadeusz Mazowiecki - the first non-communist Prime Minister in the former Eastern bloc. After describing the importance of this doctrine for Poland’s international politics after the fall of communism, we show how this utopia that became reality was undermined by the Law and Justice Party (PIS), which effectively abandoned it by choosing its opposite - the spirit of revenge, resentment and settling of scores.